Talaffuzh Niat in Prayer Worship : Sheikh Ahmad Khatib Al-Minangkabawi's Thought - Firdaus, Beni (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2021)
One of the topics of debate between the old and the young at the beginning of the 20th century was the question of talaffuzh intention. The discourse on talaffuzh intention does not only involve the scholars who are in the country, but also involves the Minangkabau cleric who lives in Mecca al Mukarramah, namely Sheikh Ahmad Khatib al-Minangkabawi. The thoughts he put forward often lead to polemics with scholars in the archipelago. One of them is about talaffuzh intention. In this article the author examines how Ahmad Khatib thinks about talaffuzh intentions and how the legal istinbâth method he uses. The purpose of this study is to explain Ahmad Khatib's thoughts about talaffuzh intentions and the legal istinbâth method he uses. This type of research is library research. The collected data were analyzed using content analysis method. Based on the research conducted, it can be concluded: according to Ahmad Khatib, the law of reciting intentions is sunnah. The legal istinbâth method he uses in this problem is the qiyâs method.Salah satu topik perdebatan antara kaum tua dan kaum muda pada awal abad ke-20 adalah persoalan talaffuzh niat. Diskursus tentang talaffuzh niat tidak hanya melibatkan para ulama yamg berada di tanah air, tapi juga melibatkan ulama Minangkabau yang bermukim di Mekah al Mukarramah yaitu Syekh Ahmad Khatib al-Minangkabawi. Pemikiran yang dikemukakannya tidak jarang menimbulkan polemik dengan ulama di Nusantara. Salah satunya adalah mengenai talaffuzh niat. Dalam artikel ini penulis meneliti bagaimana pemikiran Ahmad Khatib tentang talaffuzh niat dan bagaimana metode istinbâth hukum yang digunakannya. Adapun tujuan penelitian ini adalah untuk menjelaskan pemikiran Ahmad Khatib tentang talaffuzh niat dan metode istinbâth hukum yang digunakannya. Jenis penelitian ini adalah penelitian kepustakaan. Data yang terkumpul dianalisa dengan menggunakan metode content analysis. Berdasarkan penelitian yang dilakukan dapat disimpulkan: menurut Ahmad Khatib, hukum melafalkan niat adalah sunnah. Metode istinbâth hukum yang digunakannya dalam masalah ini adalan metode qiyâs.